Green marketing and purchase intention of green product: The role of environmental awareness - Krisdayanti Krisdayanti; Arief Widodo (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2022)
Along with the development of people's lifestyles, the concept of environmental awareness has now become part of their daily lives. For this reason, it is necessary to know the effect of green marketing on purchase intention in a green label tissue with environmental awareness as a moderation. This study uses a quantitative method by distributing questionnaires with Google Forms to 175 respondents, which are then analyzed using Moderate Analysis Regression (MRA). The results of hypothesis testing indicate that green marketing has a positive effect on purchase intention, and the consequences of the second hypothesis test indicate that environmental awareness strengthens the influence of green marketing on the customers' purchase intention. The implications of this research can provide input for companies that want to increase purchase intention of products with a green marketing strategy.